STRATEGI GURU DALAM MENGATASI KESULITAN MEMBACA PADA SISWA SEKOLAH DASAR - Adellia, Belgis; Handayani, Wianda Puspita; Aurelia, Cantika; Andrian, Firma; Adiwijaya, Satria Nugraha (FASHLUNA, 2025)
Teachers have a significant influence on changes in student behavior. Writing, reading, listening and speaking skills are important abilities that every student needs to have. Based on the results of observations at SDN 05 Metro Timur, there are still a number of students in high classes who have not mastered reading skills well, such as being unable to differentiate between the letters a and i and g and s, and still reading by spelling and not being able to read fluently. The aim of this research is to identify various strategies implemented by teachers in overcoming elementary school students' reading difficulties. The method applied in this research is descriptive qualitative, with data collection carried out through interviews, observation and documentation. The research results show that 1) the impact of reading difficulties can affect students' learning activities in class, and students who are not yet able to read will definitely be left behind when receiving and processing new knowledge. 2) The strategies implemented by the teacher include dictating and writing on the blackboard, using phonics reading methods, holding discussions, and providing motivation so that students continue to learn to read. ABSTRAK Guru memiliki pengaruh yang signifikan terhadap perubahan perilaku siswa. Keterampilan menulis, membaca, mendengarkan, dan berbicara adalah kemampuan penting yang perlu dimiliki oleh setiap peserta didik. Berdasarkan hasil observasi di SDN 05 Metro Timur, masih terdapat sejumlah siswa di kelas tinggi yang belum menguasai kemampuan membaca dengan baik., seperti ketidakmampuan membedakan huruf a dan i serta g dan s, serta masih membaca dengan cara mengeja dan belum mampu membaca dengan lancar. Tujuan penelitian ini adalah untuk mengidentifikasi berbagai strategi yang diterapkan guru dalam mengatasi kesulitan membaca siswa sekolah dasar.. Metode yang diterapkan dalam penelitian ini adalah kualitatif deskriptif, dengan pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa 1) dampak dari kesulitan membaca dapat memengaruhi aktivitas belajar siswa di kelas, dan siswa yang belum mampu membaca pasti akan tertinggal saat menerima dan memproses pengetahuan baru. 2) Strategi yang diterapkan oleh guru meliputi mendikte dan menuliskan di papan tulis, menggunakan metode membaca fonik, mengadakan diskusi, serta memberikan motivasi agar siswa terus belajar membaca.